Program Rebranding Produk Lokal Unggulan yang Berorientasi Eksport di Indonesia sebagai Upaya Strategi Marketing pada Pasar Global - Fortunisa, Ananda (LPkM Universitas Bakrie, 2019)
Brand development (rebranding) is a marketing strategy by renewing or renewing the total name, tagline, symbol, design created for the brand with the aim of developing and renewing in the minds of consumers, investors and developers. Rebranding is an effort or effort made by a company or institution to totally change or renew a brand that has been made to be better, with which cannot achieve the initial goal of a profit-oriented company. The benefit of rebranding, Larslong (2004) in Liminto (2010: 37) is that branding is not just the design of a company logo. Branding is the relationship between consumers and companies, between consumers and products or between consumers and services. This activity aims to improve the competitiveness of Indonesian products through brand enhancement and development to be more easily marketed and be able to improve the image and trust of Indonesian products in the international market. The purpose of this activity is to provide stakeholders with an understanding of the importance of brand development as part of efforts to improve the competitiveness and selling value of a product, as well as facilitate business development to build its brand in the form of structuring brand identity (logos), applications in the form of promotional materials and product packaging. Location of the activities in 6 cities, Bandar Lampung, Ambon, Yogyakarta, Pekalongan, Sukabumi, and Bandung were conducted in the second semester of 2018.